Rotational molding parameters of wood-plastic composite materials made of recycled high density polyethylene and wood particles - Arribasplata-Seguin, Adán (2021)
Recent investigations have demonstrated that it is possible to incorporate different natural fibers in the rotational molding process. In this perspective, the main purpose of this work is to study the influence of rotational molding parameters on the sintering process of composite materials made of recycled high density polyethylene and wood particles. To achieve this, an experimental procedure of three molding stages was elaborated to make wood-plastic composite materials. At each stage, it was studied the effect of a certain molding parameter on mechanical properties, while the other parameters remain constant during the molding process. The composite materials made during each stage were tensile tested to identify which of them have suitable mechanical properties and to find the most convenient molding parameters for making them. Using a stereoscope, pictures of composite materials' morphologies were taken to study the degree of sintering and determine its influence on mechanical properties. Results show that there is a very close relationship among composite materials’ morphologies, degree of sintering, rotational molding parameters and mechanical properties. In addition, it has been found that composite materials that reached the most convenient properties have a tensile strength which decreases up to 17% and an elastic modulus which increases up to 16%, in regard to a material made of neat recycled polyethylene that was molded under the same conditions. © 2021 Elsevier Ltd